Is the transit time of a meal through the small intestine related to the rate at which it leaves the stomach?. Issue 10 (October 1982) - Read, N W; Cammack, J; Edwards, C; Holgate, A M; Cann, P A; Brown, C
Abstract : Using non-invasive techniques, we investigated how varying the size or composition of a meal altered the rate at which it passed through the stomach and small intestine in normal volunteers. Increasing the size of the meal by doubling the absorbable components delayed gastric emptying, did not significantly influence the time taken for the head of the meal to reach the caecum, but retarded the entry of the bulk of the meal residues into the caecum. Incorporating fat in the meal slowed gastric emptying, but did not significantly affect small bowel transit time. The addition of the unabsorbable disaccharide lactulose (in place of an equivalent amount of sucrose) accelerated small bowel transit time, but did not significantly influence gastric emptying. Thus, our results indicated that changes in small bowel transit time could occur independently of changes in gastric emptying in normal healthy subjects.